Lisandro Inakake - Launch Website, English - Instituto de Manejo e Certificação Florestal e Agrícola (Instituto de Manejo e Certificação Florestal e Agrícola - IMAFLORA, 2019)
Lisandro Inakake de Souza talks about the plans to develop user-need driven geospatial information service and invites users to go to the Website https://servir.ciat.cgiar.org/